A home for us and a womb for her: Living the Family Integrated Care model in a Danish NICU - Ann Katrine Miranda (The Beryl Institute, 2020)
Family Integrated Care (FICare) has been widely adopted in Denmark as a framework for caring for infants in the Neonatal Intensive Care Unit (NICU), enabling parents to take on an active role in the care of their infant, while the NICU staff takes on a more supporting and educating role when possible. The purpose of this paper is to provide an autoethnographic account describing the personal experience of living in a NICU with a preterm infant for the duration of 76 days from the perspective of a first-time mother. The autoethnographic method provides the reader with a detailed description of the experience of a mother caring for her preterm baby under the conditions of living fulltime in the NICU and allows for an exploration of specific challenges related to the FICare model as it is practiced in the Danish public healthcare system. The article discusses specific challenges of the FICare model related to parental isolation as well as parent-healthcare staff interdependence and highlights reflections on its implementation that may prove valuable for healthcare professionals in the NICU setting to consider further. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens